2017
DOI: 10.1111/aas.12935
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative music application in children and adolescents – a pilot study

Abstract: Intraoperative music application in children undergoing minor surgical procedures may reduce the incidence of post-operative maladaptive behaviour within the first week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(62 reference statements)
0
2
0
2
Order By: Relevance
“…Buehler et al 22 reported that intraoperative music application in minor urogenital surgery in children reduced maladaptive behavior in the first week postoperatively but music did not affect postoperative patient pain, comfort or vomiting and nausea rates. In the study, postoperative behaviors of children receiving intraoperative music therapy were documented by their families at 7, 14 and 28 days post-surgery, using a questionnaire adapted from the ‘Post Hospitalization Behavior Questionnaire’.…”
Section: Discussionmentioning
confidence: 99%
“…Buehler et al 22 reported that intraoperative music application in minor urogenital surgery in children reduced maladaptive behavior in the first week postoperatively but music did not affect postoperative patient pain, comfort or vomiting and nausea rates. In the study, postoperative behaviors of children receiving intraoperative music therapy were documented by their families at 7, 14 and 28 days post-surgery, using a questionnaire adapted from the ‘Post Hospitalization Behavior Questionnaire’.…”
Section: Discussionmentioning
confidence: 99%
“…Because the nerves that control hand movement and coordination are involved in the operation, the doctor asked Turner to play the violin during the operation to ensure that the brain parts that control the hand's movement and coordination are not damaged. Buehler et al [43] explored the influence of external factors on postoperative recovery in inguinal hernia repair. They randomly divided the children into a control group and an experimental group.…”
Section: B Sgmo For Patientsmentioning
confidence: 99%
“…Após a indução da anestesia geral, foi realizado bloqueio caudal ou paravertebral em dose única, guiado por ultrassom, com ropivacaína 0,2% com adrenalina 1200000. Buehler et al, 2017 Intraoperative music application in children and adolescents -a pilot study.…”
Section: Títulounclassified
“…No entanto, o desempenho do bloco em crianças requer experiência e prática adequadas. Buehler et al (2017) mostrou que a ocorrência geral de pelo menos um item desadaptativo foi menor no grupo de música, com uma incidência significativamente menor no dia 7 (51% vs. 77% nos controles; P <0,01). A aplicação de música intraoperatória em submetidas a pequenos procedimentos cirúrgicos pode reduzir a incidência de comportamento desadaptativo pós-operatório na primeira semana.…”
Section: Rev Bras Anestesiolunclassified